Social Criticism Of Mochtar Lubis In Headlines About Rene Coenrad Featured In Indonesia's Raya Daily From October 1970 To January 1971 - Febbrizal Febbrizal; Abdurakhman Abdurakhman (West Science Interdisciplinary Studies, 2026)
This research investigates Mochtar Lubis' social commentary through the editorial position of Harian Indonesia Raya, focusing on the Rene Coenrad case from October 1970 to January 1971. The death of Rene Coenrad during a soccer match between students and police cadets at ITB highlighted the underlying tensions between students and the government at the outset of the New Order period, following their joint attempt to overthrow the Guided Democracy regime in 1966. This study employs historical and content analysis techniques, analysing primary sources including headlines and articles from the Indonesia Raya newspaper. The initial section examines the socio-cultural background of the Rene Coenrad case and subsequently delves into students' reactions to it. The following section examines the early New Order government and Mochtar Lubis' role at the Indonesia Raya newspaper. The central theme of this article centres on Mochtar Lubis' social commentary in connection with the Rene Coenrad case, a crucial example of escalating student-government conflicts at the beginning of the New Order period. Exploring the complex relationship between students and the government throughout Indonesia's history is deeply captivating; students have consistently played a crucial role in moulding the nation's historical context. To fully understand the social commentary in Mochtar Lubis' editorial on René Coenrad, it is crucial to understand the portrayal of contemporary events and their underlying importance.